Clustering-based analysis for residential district heating data. (1st June 2018) - Gianniou, Panagiota; Liu, Xiufeng; Heller, Alfred; Nielsen, Per Sieverts; Rode, Carsten
Highlights: K-means is used to segment heating consumption intensity and load pattern groups. A constant load profile represents most of the district heating customers. Calendar context affects load patterns and consumer behavior. Customers with high energy consumption have lower variability. Abstract: The wide use of smart meters enables collection of a large amount of fine-granular time series, which can be used to improve the understanding of consumption behavior and used for consumption optimization. This paper presents a clustering-based knowledge discovery in databases method to analyze residential heating consumption data and evaluate information included in national building databases. The proposed method uses the K -means algorithm to segment consumption groups based on consumption intensity and representative patterns and ranks the groups according to daily consumption. This paper also examines the correlation between energy intensity and the characteristics of buildings and occupants, load profiles of households, consumption behavior changes over time, and consumption variability. The results show that the majority of the customers can be represented by fairly constant load profiles. Calendar context has an impact not only on the patterns but also on the consumption intensity and user behaviors. The variability studies show that consumption patterns are serially correlated, the customers with high energy consumption have lower variability, and the consumption is more stable over time. These findings will be valuable for district heating utilities and energy planners to optimize their operations, design demand-side management strategies, and develop targeting energy-efficiency programs or policies.